Origin of ethnic name Buryat - Zoriktuev, Bulat R. (The New Research of Tuva, 2014)
The question about originsof the name ‘Buryat’ is one of the oldest ones in the Buryat studies. Article presents the results of the latest results of studies by identifying and studying a large number of new sources and the revision of the existing approaches to the disclosure of the etymology of the ethnonyms.
Keywords: Baikal; forest tribes; ethnic consolidation processes; Buryats